KORELASI LAMA PENYIMPANAN NIRA NIPAH (Nypa fruticans Wurmb.) TERHADAP RENDEMEN BIOETANOL - Freddy, Manompang; Sulaeman, Rudianda; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Nypa fruticans Wurmb producing sap that can be obtained through wiretapping fruit bunches. Nipa sap fresh taste sweet because it contains sugar which is quite high. Nipa sap is processed into bioethanol as a renewable energy source that is being developed still find obstacles in its management due to the community when the sap has been tapped then collected, indirectly sold and stored. The yield of bioethanol is one of the considerations in the process of bioethanol production from nipa sap. Nipa sap sugar levels are high it is possible to produce a high yield. This research aim to determine the effect of storage long time the sap nypa to the yield of bioethanol. This research was conducted experimentally by the method of completely randomized design (CRD) with 5 treatments and 3 replications. The treatments used were P1 = storage long for 24 hours, P2 = storage long sap for 36 hours, P3 = storage long for 48 hours, P4 = storage long sap for 60 hours, P5 = storage long sap for 72 hours. Data was analyzed by regression analysis. The results of this research shows that the nipa sap storage time significantly affect the yield of ethanol produced. The yield of the resulting fewer and fewer when the sap is stored longer. Keywords: Nypa fruticans Wurmb, Bioethanol, The Yield Of Bioethanol